2014
DOI: 10.1186/s13059-014-0432-0
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing reveals clonal evolution patterns and mutation events associated with relapse in B-cell lymphomas

Abstract: BackgroundMolecular mechanisms associated with frequent relapse of diffuse large B-cell lymphoma (DLBCL) are poorly defined. It is especially unclear how primary tumor clonal heterogeneity contributes to relapse. Here, we explore unique features of B-cell lymphomas - VDJ recombination and somatic hypermutation - to address this question.ResultsWe performed high-throughput sequencing of rearranged VDJ junctions in 14 pairs of matched diagnosis-relapse tumors, among which 7 pairs were further characterized by ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 48 publications
4
56
0
Order By: Relevance
“…Our data confirm the work by Jiang and colleagues who showed that clonal evolution occurs in DLBCL under the selection pressure of RCHOP and subsequent therapies, by showing clonal enrichment of one or more mutation in 11 of 12 paired samples (19). A repeat biopsy at the time of relapse would therefore be warranted if the tumor biology were guiding the choice of therapy.…”
Section: Socs3supporting
confidence: 89%
See 2 more Smart Citations
“…Our data confirm the work by Jiang and colleagues who showed that clonal evolution occurs in DLBCL under the selection pressure of RCHOP and subsequent therapies, by showing clonal enrichment of one or more mutation in 11 of 12 paired samples (19). A repeat biopsy at the time of relapse would therefore be warranted if the tumor biology were guiding the choice of therapy.…”
Section: Socs3supporting
confidence: 89%
“…Our work directly complements previous studies of rrDLBCL that were underpowered to detect mutations that were significantly more common at relapse (19,20). TP53 emerged as a top candidate in our analyses, an expected result that supports our analytic approach.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…10 There is typically a clonal evolution among lymphoma cells, with some heterogeneity of genes involved in lymphoma growth that might explain the chemorefractoriness and difficulties of salvage. 11 Furthermore, it has also been shown that DLBCL pathogenesis is strongly related to epigenetic perturbations and that high epigenomic heterogeneity correlated with a higher relapse rate and poor outcome. 12 These observations open the pathway to specific DNA methyltransferase and histone methyltransferase inhibitors designed to erase aberrant epigenetic programming.…”
Section: Patients With Early Relapsementioning
confidence: 99%
“…All targeted sequencing raw data files, including VDJsequencing and targeted resequencing of the UBR4 and B2M loci, have been deposited into NBCI database BioProject PRJNA240336 [50].…”
mentioning
confidence: 99%